Studi Peningkatan Kualitas Belajar melalui Analisis Gaya Belajar Individu dalam Membentuk Kompetensi Entrepreneurship - Jajat Sudrajat (The Winners, 2013)
The purpose of this study is to analyze the influence of learning styles of individuals in shaping entrepreneurial competence as a study improvement of the quality of learning. Participants of this study were students at University Telkom Business Management, Department of Telecommunications and Informatics, Bandung. This study used descriptive analytical method. Results of this study found that the effect of simultaneous greatest between individual learning styles: concrete experient (X1), reflective observation (X2), abstract conseptualization (X3), and active experimentation (X4) on the competence entrepreneurship: thinking & problem solving (Y3) relatively strong at 93.4%. This research proves that learning styles of students have an influence on the formation of entrepreneurial competence. Greatest amount of influence an individual learning styles simultaneously to the competence of entrepreneurship is 93.4%. Based on these results, it is recommended as follows: (1) the curriculum is constantly made to improve and have confidence entrepreneurial competencies (personal maturity); (2) the quality of faculty members should be improved by improving education and training, especially the training of soft skills in order to familiarize themselves to the learning style of analytical thinking can be improved; (3) facilities and infrastructure to support teaching and learning process should continue to be evaluated in order to function properly.